Sistem Nilai Pela sebagai Modal Sosial dalam rangka Penguatan Kebangsaan pada Basis Lokal di Maluku - Max Maswekan (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2020)
Indonesia is a pluralistic country in terms of ethnicity, religion, culture, language, and social system. This diversity is a blessing that is given as a potential wealth of the nation. On the one hand, this potential can be managed to strengthen nationality and people's welfare, but on the other hand, it can be a potential conflict that can weaken and even solve the disintegration of nationalism if it is not managed properly. Indonesia has a variety of local wisdom as invaluable social capital. One of them is Pela in Maluku which has a value system that is capable of marching and strengthening (integration) nationalism. The Pela value system has at least four functions that can effectively integrate (social cohesion) and strengthen national potential at the local or regional level, especially in Maluku.